Sensor-assisted push walker training for walking ability in infants aged 9-15 months: a pre-post study - Islamiyati Islamiyati; Sadiman Sadiman; Yoga Tri Wijayanti; Huminsa Ranto Morison Panjaitan; Riza Muhida; Muhammad Riza; Dandi Efendi (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Walking is a crucial milestone in an infant's gross motor development. Conventional baby walkers pose safety risks, whereas walking practice using a push walker equipped with a speed sensor allows for controlled walking exercises. Objective: This study aimed to describe changes in walking ability among infants aged 9–15 months after using a push walker with a speed sensor for 21 days. Methods: A single-group pre- and post-intervention design was employed. A purposive sample of 35 infants aged 9–15 months—who could stand but not yet walk—was selected. The intervention involved walking practice with a speed sensor-equipped push walker for 15–20 minutes, conducted in three daily sessions over 21 days. The device was kept at the respondents' homes, and usage was supervised. Data were collected through observation and measurements by enumerators. Data were analyzed descriptively using frequencies, percentages, means, and minimum/maximum values. Results: Most infants showed a positive initial response to the push walker. Nine infants (25.7%) were able to grasp the device independently upon initial introduction, while 26 infants (74.3%) required guidance. During the 21-day observation period, 13 infants (37.1%) began walking independently; the earliest onset was on day 3, with an average onset on day 12. The average walking distance increased from 1.4 m pre-intervention to 3.8 m post-intervention. Conclusion: Supervised use of a push walker with a speed sensor accelerated the development of walking ability in some infants aged 9–15 months.